Design of New N-polyether Pyrazole Derived Ligands: Synthesis, Characterization and Regioselectivity - Guerrero, Miguel; A Perez, Jose; Ros, Josep; Branchadell, Vicenc; Pellicer, Eva; Sort, Jordi; Pons, Josefina (Current Organic Synthesis, 2014)
In this paper, we present for the first time the synthesis in satisfactory yields and characterization of a new family of five Npolyetheralkyl- 3,5-pyrazole derived ligands (L1-L5) as well as regioselectivity studies by NMR techniques. Ligands L1, L2, L3/3’, and L4/4’ were obtained by N-alkylation reaction, whereas for L5 O-alkylation reaction was followed. In N-alkylation, the alkylating agent was 1-chloro-2-[2-(2-methoxyethoxy)ethoxy]ethane, NaOEt as base and dry toluene as solvent. In O-alkylation, the alkylating agent is 1- chloro-2-[2-(2-methoxyethoxy)ethoxy]ethane, metallic Na as a base and dry tetrahydrofurane as solvent. In general, the two methods lead to high yields (60-95%), with reaction times of 24 h, except for L2 (48 h). All synthesized ligands have been characterized by elemental analyses, electrospray mass spectra, infrared spectra, 1H, 13C1H and HSQC NMR spectroscopy. Furthermore, the different regioselectivity observed in the synthetic reactions of pyrazole precursors with one pyridyl substituent has been rationalized from theoretical calculations. All together proves that the different behavior depends on whether the rate determining step is the SN2 reaction or the formation of the precursor complexes between pyrazolide-Na+ chelates and the polyether chloride chain. The application of this new family in supramolecular crystal engineering is interesting due to the different bonding properties of the heteroatoms (N vs. O) present in the structure of the ligands.
Keywords: 5-pyrazole derived ligands